Extended stribeck curves for food samples. Issue 1 (22nd March 2018) - Pondicherry, Kartik S.; Rummel, Florian; Laeuger, Joerg
Abstract : Stribeck curves have long been used for understanding the lubricating behaviour of oils and greases, and in the recent years for applications ranging from ball point inks to synovial fluids. In the current work, an attempt is made to show as to what one can read from Stribeck curves of food samples such as chocolate spread, sauce etc. Additionally, the effect of saliva – human and artificial – on the frictional behaviour has also been studied. The tests were carried out on an MCR Tribometer with a ball‐on‐three‐pin configuration. Polydimethylsiloxane and glass were used to simulate soft contact conditions that exist in the human mouth. Results from the tribological tests are plotted in the form of extended Stribeck curves, wherein, the friction coefficient is plotted as a function of rotational speed. Since the tribometer is capable of speeds as low as a few nanometres per second, it is also possible to observe the build‐up of static friction and its transition into the kinetic regime of friction. Results indicate that certain aspects of the Stribeck curve can offer an insight into the correlation between the frictional behaviour of food to their sensory feel.